Students' perception on utilizing podcast in learning speaking skill - Wulan Rahmasari; Yousef Bani Ahmad; Acep Bahrum Kamil (English, 2021)
This research aimed to find out students’ perception of utilizing podcasts in learning speaking skills. The researchers used a qualitative approach and basic interpretative design to explore students’ perceptions. Three students were involved in this study. They are first-grade students of the vocational high school in the academic year 2019/2020. The data was gathered from the reflective journal and semi-structured interview. To obtain the data, the researchers analyzed it by thematic analysis. Results of this research, researchers classified three aspects that are the instruction in the podcast, the benefits of the podcast, and the use of podcast. The findings illustrated that students had a positive perception of the utilization of podcasts in learning speaking. Students perceive that podcast is interesting media because it has many contents or topics that they can listen and practice their speaking skill whenever they want. They also agree that podcast is beneficial for speaking achievement, for example, students can increase their vocabularies and word pronunciation.